Acinetobacter baumannii: A Brief Account of Mechanisms of Multidrug Resistance and Current and Future Therapeutic Management - Harmanjit Singh; Pugazhenthan Thangaraj; Amitava Chakrabarti (Journal of Clinical and Diagnostic Research, 2013)
Acinetobacter baumannii, a non-motile, glucose non fermentative, oxidase negative, encapsulated, gram-negative coccobacillus, has recently gained importance because of its increasing resistance to the available antibiotics. Three main mechanisms of resistance in A. baumannii are: enzymes inactivating antibiotics, reduced entry into the target site of bacteria and alteration of the target or cellular functions due to mutations. Multi-drug resistant A. Baumannii, including carbapenam resistant A. Baumannii, are posing a potential threat to mankind by causing lethal infections, especially in ICU set up and in patients who are on ventilators, for which our conventional antibiotics were not shown to be effective. Many reports have indicated carbapenam resistance among A. Baumannii and only colistin and tigecyclyne have shown some promise in combating this lethal microorganism.